PERSPECTIVES ON ALCOHOLIC DRINK INTAKE AMONG PREGNANT WOMEN - Ribeiro Dias, Daniele; Herdy Alves, Valdecyr (Health and Society, 2023)
The present study is an integrative review that aimed to analyze Brazilian scientific production on the intake of alcoholic beverages during pregnancy and discuss the role of the multidisciplinary team in the prenatal period. This is qualitative research, of a descriptive bibliographic nature. Data collection took place from August to November 2022, through an electronic search in the LILACS, SCIELO and BDENF virtual databases. After the searches, twelve productions were selected. It was possible to identify three thematic groups, namely: performance of the multidisciplinary team in prenatal care, consequences of alcohol consumption during pregnancy and predisposing factors to alcohol consumption during pregnancy. It is concluded that professional unpreparedness makes it difficult to identify the use/abuse of alcohol during pregnancy. Therefore, there was a need to train and raise awareness among professionals working in prenatal care about the importance of this topic and the focus of attention on tracking this habit. Alcohol consumption during pregnancy can harm not only the mother’s health but can also cause several health problems for the newborn, therefore health education and prevention actions are essential.